PENINGKATAN KETERAMPILAN MENULIS TEKS NEGOSIASI MENGGUNAKAN MODEL EXAMPLE NONEXAMPLE PADA SISWA SMAK - yarso, Elanatasia; Salem, Laurensius; Patrianto, Patrianto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is initiatedby the lack of student skills in writing. This can be proved from the average student's scorewhichis below 70; the criteria of minimal submission, the students are less skilled in pouring ideas into their writing. This research is focused on writing material on negotiating text using an example nonexample learning model. The problem formulated in this study, "How is the planning, implementation and learning outcomes of using a nonexample learning model. The purpose of the study is to describe the planning, implementation and learning outcomes using the example Nonexample learning model to improve the learning of writing negotiation text for students of Grade X Social Science Class in SMAK Santo Thomas AquimasBengkayang. The method used for this collection is a descriptive method. The design is class action research (PTK). The techniques used are direct communication techniques in the form of interview guidelines and documentation studies. The tools used for data collection in the form of observation guidelines are IPPKG 1 and IPKG 2 and the Student Assessment sheet. The analytical techniques used in this study are qualitative descriptive. The results the students gained in the learning process skills of writing negotiation text using example Nonexample learning models increased ranging from pre-cycles, cycle I, cyclesII , and cycle III. The results of the increase before carrying out the average action value of the student is 64.28% and there are 2 students completed. After the research carried out on the cycle I average grade is 80.03%, and there are 21 students who complete. In the cycle III the average student score increased to 89.76% and there were 22 students who completed, so from each cycle experienced an excellent improvement.Keywords: Writing Skills, Negotiative Text and learning Example NonexampleModel.